Rencana Pengelolaan Sampah Melalui Optimalisasi Bank Sampah Pada Kelurahan Pudakpayung, Kecamatan Banyumanik - Gitta Ayu Pavitasari; Bintang Septiarani (Jurnal Riptek, 2023)
Semarang city is an area with an increasing number of residents increasing from year to year. This causes the generation of waste generated by households is increasing. To overcome the generation of waste that accumulates in the landfill Jatibarang, Semarang City Government conducted a variety of waste management, one of which is the waste bank. Pudakpayung village in Banyumanik District is one of the villages in Semarang that has empowered the waste bank program to manage waste from upstream. Operationally, the waste bank in Pudakpayung village has not been running optimally. The purpose of this study is to formulate the substance of the waste management plan through the optimization of waste banks in Pudakpayung Village. The method used is a combination of quantitative and qualitative with field observation activities, interviews related to waste bank management, and the dissemination of questionnaires about the role of the community. Based on the results of the study, obtained waste generation in Pudakpayung village of 0.711 kg/person/day with a composition of 61% organic waste and 39% inorganic waste. Meanwhile, there are 113,690 kg/month of potential waste in the waste bank by the people of Pudakpayung Village. However, 8 (eight) waste bank units in Pudakpayung Village received a total waste generation of 2,213.4 kg/month. Waste banks reduce waste by 1.91% of total potential waste entering waste banks. At the end of the Planning year, the entire community of Pudakpayung village became waste bank customers to participate in reducing potential waste entering the waste bank. To realize this, operational and non-operational technical planning is designed to realize waste management through optimization of waste banks.